2013
DOI: 10.1057/jdg.2013.31
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance reforms in emerging countries: A case study of Bangladesh

Abstract: This article considers three related research questions, all in the context of an emerging economy, Bangladesh: What is the history of corporate governance (CG) reform in Bangladesh? What explains the introduction of CG guidelines in Bangladesh? and How have the country-level initiatives to improve CG influenced the firm-level practices of CG? By analysing the agency environment and CG reforms in Bangladesh, this article finds that, in spite of the number of reform initiatives undertaken since the early 1990s,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Given Bangladesh’s political, cultural and economic forces, the market offers little protection to minority shareholders (Solaiman, 2006), challenging the efficacy of the Anglo-American-style CG Guidelines (Li and Harrison, 2008; Haxhi and van Ees, 2010). An undeveloped capital market, together with a high reliance on bank financing, limited monitoring, a poor legal framework (Siddiqui, 2010) and weak insider trading legislation and enforcement (Biswas, 2012), means that CG monitoring and enforcement mechanisms are weak, allowing many wrongdoers to go undetected (Uddin and Choudhury, 2008; World Bank, 2009). These tensions are further complicated by the prevalence of corruption in Bangladesh, which is one of the “most important determinants of social and environmental performance” in emerging markets (Claessens and Yurtoglu, 2013, p. 19)[5].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Given Bangladesh’s political, cultural and economic forces, the market offers little protection to minority shareholders (Solaiman, 2006), challenging the efficacy of the Anglo-American-style CG Guidelines (Li and Harrison, 2008; Haxhi and van Ees, 2010). An undeveloped capital market, together with a high reliance on bank financing, limited monitoring, a poor legal framework (Siddiqui, 2010) and weak insider trading legislation and enforcement (Biswas, 2012), means that CG monitoring and enforcement mechanisms are weak, allowing many wrongdoers to go undetected (Uddin and Choudhury, 2008; World Bank, 2009). These tensions are further complicated by the prevalence of corruption in Bangladesh, which is one of the “most important determinants of social and environmental performance” in emerging markets (Claessens and Yurtoglu, 2013, p. 19)[5].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In this regard, the board's image is factored against the percentage of outside or independent directors (Balachandran & Faff, 2015;Balc et al, 2013;Bauer et al, 2008; Organisation for Economic Co-operation and Development [OECD], 2015;Stein, 2008;Uddin & Choudhury, 2008). Independent directors should not be employees of the organisation and should have no relationship with the organisation, and they are expected to act as informants to the organisation (Biswas, 2015;Rashid, 2015b). Previous research has found mixed results about the effects of independent directors on MFIs' performance.…”
Section: Theoretical Discussion and Hypothesis Developmentmentioning
confidence: 99%
“…This practice is not uncommon in many Anglo-American nation-states, i.e. Australia, the UK, New Zealand, the US, and Canada (Biswas, 2015). The two-tier or monitoring board practices are absent in the microfinance sector (Hasan et al, 2019).…”
Section: Microfinance Board Practices In Bangladeshmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth across all sectors leads to an increasing demand for accounting services (de Lange et al , 2015; Stainbank and Tewari, 2014). While academic research in accounting-related fields in Bangladesh has been expanding, this study has largely focused on governance issues (see Biswas, 2015; Biswas and Bala, 2016) and CSR reporting (see Belal and Owen, 2007; Khan et al , 2011; Islam and Dellaportas, 2011; Muttakin et al , 2015). Empirical research on CPD for the accounting profession in Bangladesh has been non-existent.…”
Section: Introductionmentioning
confidence: 99%